Metal-Free, Bio-Triboelectric Nanogenerator Based on a Single Electrode of Bacterial Cellulose Modified with Carbon Black - Freire, Andre L.; Lima, Lais R.; Candido, Iuri C. M.; Silva, Luygui G. [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Carrilho, Emanuel; Oliveira, Thais L.; de Oliveira, Luiz Fernando C.; Barud, Hernane S.; de Oliveira, Helinando P. (MDPI, 2024)
Developing metal-free electrodes for prototypes of bio-based devices is an essential step in producing non-toxic components for implantable devices and wearables. In particular, the advancement in self-powered devices is a hot topic for several applications due to the possibility of creating free-battery devices and sensors. In this paper, the modification of bacterial cellulose by the progressive incorporation of carbon black (a conductive filler) was explored as a prototype for bio-based electrodes for triboelectric nanogenerators. This process was controlled by the percolation pathways’ activation through the contact of carbon black grains with the bacterial cellulose membrane, which represents a critical step in the overall process of optimization in the power output performance, reaching an open circuit voltage value of 102.3 V, short circuit current of 2 μA, and power density of 4.89 μW/cm2.
Keywords: bacterial cellulose; Ecoflex; energy harvesting; triboelectric